Review of S. Trubeta’s Physical Anthropology, Race and Eugenics in Greece (1880s-1970s) - Savvakis, Manos (Historein, 2014)
Sevasti Trubeta, Physical Anthropology, Race and Eugenics in Greece (1880s-1970s), Brill: Leiden, 2013. 340 pp.